2014
DOI: 10.2131/jts.39.785
|View full text |Cite
|
Sign up to set email alerts
|

Detection of initiating potential of non-genotoxic carcinogens in a two-stage hepatocarcinogenesis study in rats

Abstract: -We previously reported a toxicogenomics-based prediction model for hepatocarcinogens in which the expression patterns of signature genes following repeated doses of either genotoxic or nongenotoxic compounds were similar. Based on the results of our prediction model, we hypothesized that repeated doses of non-genotoxic carcinogens might have initiating potential. Here, we conducted a twostage hepatocarcinogenesis study in rats exposed to the initiating agent nitrosodiethylamine (DEN), and hepatotoxic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Serum biochemistry is an important parameter for the diagnosis of liver diseases and for the assessment of the degree of liver damage [ 57 ]. Plasma levels of liver enzymes such as ALT, AST, and ALP, which are known hallmarks of TAA toxicity, are increased [ 58 , 59 ]. Similar results were observed in the present study where the TAA group showed considerable elevations in serum levels of ALT, AST, ALP, total proteins, and globulin compared to the control in accordance with previous findings [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum biochemistry is an important parameter for the diagnosis of liver diseases and for the assessment of the degree of liver damage [ 57 ]. Plasma levels of liver enzymes such as ALT, AST, and ALP, which are known hallmarks of TAA toxicity, are increased [ 58 , 59 ]. Similar results were observed in the present study where the TAA group showed considerable elevations in serum levels of ALT, AST, ALP, total proteins, and globulin compared to the control in accordance with previous findings [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that it is difficult to find the relationship between the potential to induce spindle checkpoint dysfunction and genotoxic potential of renal carcinogens. Of note, we have shown disruption of spindle checkpoint function in liver cells after repeated 28-day administration of non-genotoxic hepatocarcinogens, i.e., thioacetamide and methapyrilene, in rats (Kimura et al, 2015a(Kimura et al, , 2015bOmura et al, 2014). These results suggest that spindle checkpoint dysfunction may be caused by carcinogens without relationship to their genotoxic potential.…”
Section: Discussionmentioning
confidence: 68%
“…94,95 Despite the fact that some of the chemical hepatocarcinogenesis events remain uncertain, the multistage process-Initiation ⇒ Promotion ⇒ Progression-is an accepted theory. 72,96 Its complexity can only be studied in vivo involving all aspects of exposure and target organ biology. 96 Regarding DEN, if it is injected into younger mice (less than 2 weeks), it acts as a complete carcinogen, due to higher hepatocyte proliferation rates in the juvenile.…”
Section: Experimentally Induced Liver Tumorsmentioning
confidence: 99%